2020
DOI: 10.3904/kjim.2018.326
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of postoperative atrial arrhythmias in patients who underwent lung transplantation

Abstract: Background/Aims: Atrial arrhythmia (AA) occasionally occurs after lung transplantation (LT); however, risk factors for AA and their impact on clinical outcomes are inconsistent. We aimed to investigate the incidence, predisposing factors, and clinical outcomes of AA after LT. Methods: We retrospectively evaluated 153 consecutive patients who underwent LT between January 2010 and August 2016. An AA episode was defined as a documented atrial fibrillation (AF), atrial flutter, or atrial tachycardia on 12-lead ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The rates of reexploration, tracheostomy, and grade 3 primary graft dysfunction at 72 h were 10%, 11%, and 13%, respectively. Intensive care unit length of stay was 6 (4-8) d, whereas the total length of stay was 14 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) d. Furthermore, beta-blockers and amiodarone were prescribed at the time of discharge in 67% (41) and 33% (20) of the patients who received PVI/LAL, respectively. Two (3%) of the lung transplant recipients in the PVI/LAL group were in atrial fibrillation at their 1-y follow-up visit, as shown in Table 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rates of reexploration, tracheostomy, and grade 3 primary graft dysfunction at 72 h were 10%, 11%, and 13%, respectively. Intensive care unit length of stay was 6 (4-8) d, whereas the total length of stay was 14 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) d. Furthermore, beta-blockers and amiodarone were prescribed at the time of discharge in 67% (41) and 33% (20) of the patients who received PVI/LAL, respectively. Two (3%) of the lung transplant recipients in the PVI/LAL group were in atrial fibrillation at their 1-y follow-up visit, as shown in Table 5.…”
Section: Resultsmentioning
confidence: 99%
“…Addition of anticoagulation to the immunosuppressive regimen of postlung transplant recipients with late atrial fibrillation can complicate the care because of the need for biopsies and drug-drug interactions. [10][11][12][13][14][15][16][17][18] Yersai et al 8 showed that patients with preexistent atrial fibrillation who undergo lung transplantation have prolonged hospital stays and have more readmissions in the first posttransplant year. Therefore, it is ideal to address this during the lung transplant procedure to minimize the risk of recurrence of late atrial fibrillation and related sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial arrhythmias (AAs), such as atrial fibrillation, atrial flutter, and atrial tachycardia, are common in the early postoperative phase after LT, occurring in 25% to 45% of patients [ 78 - 80 ]. A South Korean study showed that post-LT AAs occurred in 46 (30%) of 153 consecutive LTRs.…”
Section: Cardiovascular and Metabolic Complicationsmentioning
confidence: 99%
“…A South Korean study showed that post-LT AAs occurred in 46 (30%) of 153 consecutive LTRs. Preoperative higher right atrial pressure and longer mechanical ventilation were independent risk factors for AAs, which were associated with worse outcomes after LT [ 80 ].…”
Section: Cardiovascular and Metabolic Complicationsmentioning
confidence: 99%
“…Red blood cell transfusion has been shown to modulate inflammation by elevating plasma levels of inflammatory markers, thereby increasing the occurrence of postoperative AF ( 33 ). A retrospective study identified prolonged mechanical ventilation as an independent risk factor for postoperative arrhythmias, including AF ( 34 ). Mechanical ventilation induces changes in intrathoracic pressure, and both intermittent positive-pressure ventilation and positive end-expiratory pressure contribute to elevated right atrial pressure and heightened sympathetic activity, predisposing individuals to POAF ( 35 ).…”
Section: Introductionmentioning
confidence: 99%